2022
DOI: 10.1021/acsapm.2c00529
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Triphenylamine-Based Nanoporous Organic Polymers for Adsorption/Separation of C1–C3 Hydrocarbons and CO2 in Natural Gas

Abstract: The development of porous organic polymers with high gas adsorption and separation performances by a facile preparation process has progressively addressed the urgent demand for cost-effective adsorbents employed in energy-efficient purification and recovery processes. However, these polymeric materials are still poorly developed for the practical adsorption and separation of light C1–C3 hydrocarbon components, such as methane (CH4), ethane (C2H6), and propane (C3H8), from natural gas under ambient conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Furthermore, we observed that CNOP-2 showed higher capacities and lower Q st for C 2 H 6 , CO 2 , and CH 4 than CNOP-1, which is ascribed to the higher BET surface area and larger pore sizes of CNOP-2. This phenomenon has also been reported in previously published works. ,,, …”
Section: Resultssupporting
confidence: 91%
“…Furthermore, we observed that CNOP-2 showed higher capacities and lower Q st for C 2 H 6 , CO 2 , and CH 4 than CNOP-1, which is ascribed to the higher BET surface area and larger pore sizes of CNOP-2. This phenomenon has also been reported in previously published works. ,,, …”
Section: Resultssupporting
confidence: 91%
“…The C 3 H 8 , C 2 H 6 , CO 2 , and CH 4 adsorption uptakes of CNOP-5 are listed in Table S1. CNOP-5 can take up C 3 H 8 and C 2 H 6 of 174.1 and 115.4 cm 3 /g, respectively, at 273 K and 101 kPa, surpassing the previously reported NOPs such as CNOPs (76.8−99.5 and 58.2−76.4 cm 3 •g −1 ), 2 ANOPs (109.4−134.9 and 78.5−90.2 cm 3 •g −1 ), 24 and PANs (53.8− 143.2 and 44.8−108.1 cm 3 •g −1 ). 3,25,26 Because of physisorption, the four gas uptakes of CNOP-5 exhibited a downward trend with the temperature from 273 to 298 K. As displayed in Table S1, we observed C 3 H 8 and C 2 H 6 capacities of 127.0 and 82.4 cm 3 /g at 101 kPa and 298 K, respectively.…”
Section: T H Imentioning
confidence: 76%
“…3,25,26 Because of physisorption, the four gas uptakes of CNOP-5 exhibited a downward trend with the temperature from 273 to 298 K. As displayed in Table S1, we observed C 3 H 8 and C 2 H 6 capacities of 127.0 and 82.4 cm 3 /g at 101 kPa and 298 K, respectively. These capacities can compete with the previously reported NOPs, as shown in Figure 3(c), such as CNOPs (62.7−82.1 and 47.2− 60.0 cm 3 •g −1 ), 2 ANOPs (82.4−97.9 and 57.7−64.6 cm 3 •g −1 ), 24 PANs (43.9−119.0 and 29.1−84.2 cm 3 •g −1 ), 3,25,26 and sPIs (38.8−44.8 and 27.7−35.6 cm 3 •g −1 ). 11 Simultaneously, CNOP-5 uptake 48.1 cm 3 /g CO 2 under ambient conditions, which is higher than for sPANs (21.1−24.4 cm 3 /g), 1 PMOPs (40.7−41.5 cm 3 /g), 27 ANOP-M (40.6 cm 3 /g), 24 and 3AM2CL (13.4 cm 3 /g).…”
Section: T H Imentioning
confidence: 76%
See 1 more Smart Citation
“…Microporous organic polymers (MOPs) with high microporosity, excellent gas uptakes, and low isosteric heat of adsorption for CO 2 have been developed to address these shortcomings. Simultaneously, MOPs have also shown extensive applications, including the adsorption/separation of other simple gases (e.g., C 2 H 6 , CH 4 , and N 2 ), [2][3][4][5] catalysis, [6][7][8][9][10][11] sensors, [12][13][14] recovery of gold, 15,16 and water treatment. [17][18][19] Due to their excellent physicochemical properties and high porosity, more attention was focused on the design and development of MOPs to adsorb and separate simple molecular gases (such as CO 2 , C 2 H 6 , and CH 4 ) in science and industry.…”
Section: Introductionmentioning
confidence: 99%